Ekstraksi Silika Berbahan Dasar Coal Fly Ash Menggunakan Natrium Hidroksida - M.Bagas Ikmal R; Mohammad Daffa; Nurul Widji Triana (Jurnal Serambi Engineering, 2025)
The presence of fly ash waste will have a negative impact on the environment so that it is necessary to handle it by utilizing fly ash waste. Silica purification by extracting silica from coal fly ash aims to minimize the levels of unnecessary metal oxides (impurities). This study aims to determine the characteristics of silica produced from fly ash waste, determine the best extraction conditions to produce silica and determine the effect of extraction pH on the silica produced. Silica extraction includes several processes including leaching, extraction, and precipitation. In this study, the manufacture of silica gel begins with washing fly ash with HCl. Silica is extracted using 3M NaOH with time variations of 100 minutes, 120 minutes and 140 minutes. Furthermore, the silica in the filtrate is precipitated with 1M HCl with a pH range of 3.4, and 5 and an aging process of 18 hours and dried using an oven and characterized with an XRF instrument. The results of this study indicate that the closer to neutral the addition of HCl pH used, namely 5, the higher the mass of silica from the extraction obtained up to a maximum at an extraction time of 120 minutes with a silica yield of 63.42%. Extraction with a time of 100 minutes and 140 minutes showed that the mass of silica from the extraction obtained was lower along with the increasing acidity of the addition of HCl. The results of the water content test obtained 1.53% and ash content of 9.345% of the silica produced met the requirements of the Indonesian National Standard (SNI) No. 06-2477-1991.